PERIODIC SOLUTION OF NONLINEAR INTEGRO-DIFFERENTIAL EQUATION WITH NONLINEAR BOUNDARY CONDITION - BUTRIS, RAAD NOORI; AKREYI, MAYAN. S. (E-Jurnal Matematika; Vol 14 No 2 (2025)DO - 10.24843/MTK.2025.v14.i02.p478, 2025)
In this paper we study the existence and approximation of the periodic solution of nonlinear   integro-differential equation with nonlinear boundary condition by assuming the function  is a measurable at  and bounded by Lebesgue integrable function which has the weaker conditions. The numerical –analytic method has been used to study the periodic solutions of ordinary differential equations which were introduced by Samoilenko.